Peranan Data Warehouse, Software, dan Brainware Terhadap Pengambilan Keputusan (Literature Review Executive Support Sistem For Business) - Yosef Estrada Yosef (Institute of Information Technology and Social Science (IITSS), 2020)
In decision-making activities, a manager needs information, because with information, effective and efficient problem solving will be achieved in meeting existing needs. Information systems can streamline and speed up reaction times to environmental changes, and help companies achieve competitiveness. This software (DSS application) functions in giving commands to the computer, so that the computer functions optimally - in sync with the user's wishes. Meanwhile, a data warehouse is a centralized and integrated place for storing company or institutional data, and is arranged in such a way that it really supports the decision-making process, by providing input to application software. An application software requires a data warehouse in order to carry out the process accurately. Reliable and professional brainware will streamline all business interests, with support for every decision. Every business actor always competes with other business actors. The use of information technology, in this case a decision support system, is strategic because it is used not only for company operations but also to win the competition. The role of information systems in a company is important because of its ability to assist management in the process of making economic decisions. Keyword: Data Warehouse, Software, Brainware dan pengambilan keputusan.